Optimization and Evaluation of Al18F Labeling Using a NOTA—or RESCA1-Conjugated AE105 Peptide Antagonist of uPAR - Jeppesen, Troels E.; Simón, Marina; Torp, Josephine; Knudsen, Line B. S.; Leth, Julie Maja; Crestey, François; Ploug, Michael; Jørgensen, Jesper T.; Madsen, Jacob; Herth, Matthias M.; Kjaer, Andreas (Frontiers in Nuclear Medicine, 2021)
Fluorine-18 displays almost ideal decay properties for positron emission tomography (PET) and allows for large scale production. As such, simplified methods to radiolabel peptides with fluorine-18 are highly warranted. Chelation of aluminium fluoride-18 towards specific peptides represents one method to achieve this. With the current methods, chelation of aluminium fluoride-18 can be achieved using NOTA-conjugated peptides. However, the heating to 90-100°C that is required for this chelation approach may be deleterious to the targeting moiety of the probe. Recently, a new chelator, RESCA1, was developed allowing Al18F chelation at room temperature. Here, we optimize the labelling procedure enabling high chelation efficacy of fluoride-18 at 22 °C, even at full batch labelling. The optimized procedure was tested by Al18F-labelling of RESCA1-AE105—a uPAR targeting peptide. NOTA-AE105 was also labelled with Al18F, and the two peptides were compared head-to-head. [18F]AlF-NOTA-AE105 and [18F]AlF-RESCA1-AE105 could be produced in equal radiochemical yields (RCY), radiochemical purities (RCP) and molar activities. Additionally, the two peptides showed comparable binding affinity to uPAR and uptake in cells expressing the uPAR, when evaluated in vitro. Overall, we found that the performances of [18F]AlF-NOTA-AE105 and [18F]AlF-RESCA1-AE105 were grossly comparable, but importantly RESCA1 can be labelled with aluminium fluoride-18 at 22°C. Consequently, this study showed that RESCA1 is superior to NOTA with respect to Al18F chelation of temperature sensitive molecules, such as thermolabile peptides and proteins as well as that full batch chelation of RESCA1 with fluoride-18 is possible.